Biomarkers for immune checkpoint inhibition in non–small cell lung cancer (NSCLC). Issue 2 (6th November 2019) - Bodor, J. Nicholas; Boumber, Yanis; Borghaei, Hossein
Abstract : The emergence of immunotherapy has dramatically changed how non–small cell lung cancer is treated, and longer survival is now possible for some patients, even those with advanced disease. Although some patients achieve durable responses to checkpoint blockade, not all experience such benefits, and some suffer from significant immunotoxicities. Given this, biomarkers that predict response to therapy are essential, and testing for tumor programmed death ligand 1(PD‐L1) expression is the current standard. The extent of PD‐L1 expression determined by immunohistochemistry (IHC) has demonstrated a correlation with treatment response, although limitations with this marker exist. Recently, tumor mutational burden has emerged as an alternative biomarker, and studies have demonstrated its utility, irrespective of the PD‐L1 level of a tumor. Gene expression signatures, tumor genotype (such as the presence of an oncogenic driver mutation), as well as the density of tumor‐infiltrating lymphocytes in the tumor microenvironment also seem to affect response to immunotherapy and are being researched. Peripheral serum markers are being studied, and some have demonstrated predictive ability, although most are still investigational and need prospective validation. In the current article, the authors review the biomarker PD‐L1 as well as other emerging and investigational tissue‐based and serum‐based markers that have potential to better predict responders to immunotherapy. Abstract : Immunotherapy has dramatically changed how advanced non–small cell lung cancer is treated, and longer survival is now possible for some patients, although not all patients benefit from these agents, and some suffer toxicities, highlighting the importance of biomarkers that predict efficacy. This article reviews several biomarkers, including programmed death ligand 1, as well as other emerging and investigational tissue‐based and serum‐based markers that have potential to better predict responders to checkpoint inhibition.